How to do nothing eaudiobook Resisting the attention economy. - Odell, Jenny (HighBridge Audio, 2019)
A galvanizing critique of the forces vying for our attention-and our personal information-that redefines what we think of as productivity, reconnects us with the environment, and reveals all that we've been too distracted to see about ourselves and our world Nothing is harder to do these days than nothing. But in a world where our value is determined by our 24/7 data productivity . . . doing nothing may be our most important form of resistance. So argues artist and critic Jenny Odell in this field guide to doing nothing (at least as capitalism defines it). Odell sees our attention as the most precious-and overdrawn-resource we have. Once we can start paying a new kind of attention, she writes, we can undertake bolder forms of political action, reimagine humankind's role in the environment, and arrive at more meaningful understandings of happiness and progress. Far from the simple anti-technology screed, or the back-to-nature meditation we hear so often, How to do Nothing is an action plan for thinking outside of capitalist narratives of efficiency and techno-determinism. Provocative, timely, and utterly persuasive, this book is a four-course meal in the age of Soylent.